PENINGKATAN DUKUNGAN INFRASTRUKTUR DALAM PENGEMBANGAN PARIWISATA DI LABUAN BAJO - Chairullah; Djunaedi, Achmad (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
The central government, through several ministries and agencies, has completed major infrastructure development in Labuan Bajo with a substantial budget. However, problems have emerged after these infrastructure assets were handed over to the local government for management. This is evident in the underutilization of several facilities, despite their potential to significantly support tourism activities, boost the local economy, and increase regional revenue. Some facilities have even deteriorated due to inadequate maintenance, indicating that infrastructure support for tourism remains suboptimal. This study aims to evaluate the extent to which infrastructure supports tourism activities in Labuan Bajo. A descriptive qualitative method is employed, involving observations of infrastructure developed by the central government between 2020 and 2024, as well as interviews with infrastructure managers. The findings reveal that the suboptimal performance of infrastructure support is influenced by several factors, including inadequate infrastructure management quality, the lack of collaboration or partnership by the local government in managing and utilizing infrastructure, limited local government budgets for operation and maintenance, and a shortage of personnel assigned according to service needs and risk levels.